Polyurethane acrylate resin as well as preparation method and application thereof
By using UV glue prepared from polyurethane acrylate resin containing more branches, the problem in the existing technology that the CFG coating is easy to break and fog when folded outward at low temperatures is solved, and the thickness at -20°C is >150μm. The coating has the performance of no fogging, no breaking and no wrinkles when folded outward 200,000 times.
Patent Information
- Application Number
- CN202310883708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to maintain the properties of fog-free, fracture-free and wrinkle-free when the CFG coating with a thickness of >100 μm is folded 200,000 times at -20°C.
Using polyurethane acrylate resin containing more branches, triisocyanate, fatty alcohol, aliphatic saturated polyester resin or polyether glycol, diluting monomer and hydroxyl-containing acrylate monomer are used as raw materials to prepare UV glue. Fill in CFG groove.
At -20°C, when the coating thickness is 150 μm, it can be folded 200,000 times without fogging, wrinkles, or breaks, which significantly improves the low-temperature bending performance.
Smart Images

Figure BDA0004345839120000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resin synthesis, and relates to a polyurethane acrylate resin and a preparation method and application thereof, and specifically relates to the synthesis of a polyurethane acrylate resin used for a coating having high elasticity and resistance to low-temperature external folding, and its application in CFG (central foldable glass) groove filling. Background Art
[0002] With the development of display technology, the performance requirements for the screen in display devices are gradually increasing. And with the expansion of application scenarios, ultra-thin glass-based flexible display panels can be applied to foldable mobile phones, laptops and various curled display devices.
[0003] In order to meet the bendability requirements, the bending area of the glass must be very thin. Currently, there are two process routes: one is to thin the entire glass (UTG), and the other is to thin only the middle part (CFG).
[0004] UTG (integrally bendable glass) has uniform thickness, high appearance flatness, good optical effect, simple production process, and high yield rate of finished products with film or coating. However, due to the overall thinness of the glass and poor impact resistance, the glass surface cannot be directly facing the user and needs to be filmed or coated with a protective coating, and the texture is poor.
[0005] CFG (central bendable glass) only thins the glass in the bending area. The glass is thick on both sides and thin in the middle. The overall impact resistance is good (except in the middle), and the glass surface can be directly facing the user. However, when CFG is prepared, the thickness of the glass on both sides is generally 70-200μm, and the middle is only 30μm, and the thickness difference is large. Thermosetting polyurethane has good performance in various aspects, but it contains solvents and is difficult to fill the groove area. Although the compensating coating method can improve the groove filling property, the groove area is difficult to align, resulting in a low overall yield. Solvent-free UV light-curing glue is used to adhere to the release film for curing. Because it is a closed curing, the glue is fixed between the release film and CFG, and will not flow during curing. The filling property is excellent and the overall thickness of the finished product is uniform.
[0006] Since CFG is used for flexible display, it needs to undergo rigorous environmental testing. At the same time, CFG faces the customer with the glass surface, and the coating is bent outwards. In addition, the coating in the groove area is thicker. Most domestic and foreign UV glues cannot meet the requirement of 200,000 times of folding outwards at low temperature (-20℃) when the coating is thicker (≥60um). Generally, after bending for hundreds to thousands of times, the coating will break or form microcracks and fog due to the decrease of elongation at break due to hardening at low temperature, or wrinkles will appear in the bending area due to poor low-temperature recovery (if it is slight, it can be restored to normal temperature). Although optical pressure-sensitive adhesive (OCA) can meet the low-temperature bending requirements, it has a low modulus and is sticky, so it cannot be used for CFG coating.
[0007] Therefore, it is desirable in the art to develop a polyurethane acrylate resin that can be used for CFG coating. Summary of the invention
[0008] In order to meet the requirements of -20℃, coating thickness >100μm, and no cracks or creases when folded 200,000 times, manufacturers generally use polyurethane acrylate resin in combination with low glass transition temperature monomers for preparation. The low glass transition temperature monomers are mostly long-chain aliphatic and other monofunctional acrylates, such as isooctyl acrylate, butyl acrylate, isobutyl acrylate, lauric acrylate, etc. Due to their low functionality and large addition amount, the monomer conversion rate is too low when simply irradiated with ultraviolet light, and there is a lot of residue in the coating after curing, which affects the coating performance.
[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a UV coating for CFG which can meet the requirements of having a thickness of more than 150 μm at -20°C and being bent more than 200,000 times in the case of being folded outward without fogging or breaking. Compared with ordinary polyurethane acrylate, the polyurethane acrylate resin provided by the present invention has a lower glass transition temperature and better low-temperature bendability because it contains more side chains. The polyurethane acrylate resin provided by the present invention is prepared into UV glue for CFG groove filling. When the coating thickness is 150 μm, it can be folded outward 200,000 times at -20°C without fogging, wrinkling or coating breakage.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a polyurethane acrylate resin, wherein raw materials for preparing the polyurethane acrylate resin include triisocyanate, fatty alcohol, aliphatic saturated polyester resin or polyether diol, a diluent monomer, and a hydroxyl-containing acrylate monomer.
[0012] Compared with conventional polyurethane acrylate resins, the polyurethane acrylate resin provided by the present invention has more side chains and a lower glass transition temperature. When applied to CFG coatings, the side chains provided by the monomers are introduced into the main chain of the resin. Since the resin has a larger molecular weight and higher functionality, the coating has a higher degree of curing, less free monomers after curing, and the overall performance of the coating is excellent.
[0013] In the present invention, the main structure of the polyurethane acrylate resin is hydroxy acrylate-triisocyanate (-fatty alcohol)-[aliphatic saturated polyester resin or polyether diol-triisocyanate (fatty alcohol)] n -Hydroxy acrylate, wherein n is 1, 2, 3, 4, 5, ....., the larger n is, the greater the viscosity of the resin is.
[0014] Preferably, the triisocyanate comprises hexamethylene diisocyanate trimer (HDI trimer) and / or hexamethylene diisocyanate biuret (HDI biuret).
[0015] Preferably, the fatty alcohol is a monofunctional alcohol, including any one or a combination of at least two of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol or an alcohol having 5 to 18 carbon atoms (e.g., 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18), preferably any one or a combination of at least two of branched alcohols having 4 to 18 carbon atoms.
[0016] Preferably, the number average molecular weight of the aliphatic saturated polyester resin is 200-4000, for example, 200, 500, 800, 1000, 1500, 2000, 2500, 3000, 3500 or 4000, etc., preferably 500-2000.
[0017] The number average molecular weight of the polyether diol is 200-4000, for example, 200, 500, 800, 1000, 1500, 2000, 2500, 3000, 3500 or 4000, etc., preferably 500-2000.
[0018] Preferably, the diluent monomer is a monofunctional acrylate that does not react with isocyanate or hydroxyl. The diluent monomer mainly plays a diluting role during the reaction.
[0019] Preferably, the diluent monomer comprises tetrahydrofuranyl acrylate (THFA) and / or ethoxyethoxyethyl acrylate (EOEOEA).
[0020] Preferably, the hydroxyl-containing acrylic acid ester monomer includes any one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, caprolactone acrylate or caprolactone methacrylate, or a combination of at least two thereof.
[0021] Preferably, the molar ratio of the fatty alcohol to the triisocyanate is 1:(0.9-1.1), such as 1:0.9, 1:1 or 1:1.1, etc., preferably 1:1.
[0022] Preferably, the molar ratio of the aliphatic saturated polyester resin or polyether diol to the triisocyanate or hydroxyl-containing acrylate monomer is n:(n+1):2, wherein n is 1-5 (e.g., 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc.).
[0023] Preferably, the raw materials for preparing the polyurethane acrylate resin also include a drying agent.
[0024] Preferably, the drier comprises an organotin drier and / or an organobismuth drier.
[0025] Since the polymerization inhibitor has been added to the purchased monomers of the present invention, the polymerization inhibitor is not added separately in the present invention.
[0026] In a second aspect, the present invention provides a method for preparing the polyurethane acrylate resin as described in the first aspect, the preparation method comprising the following steps:
[0027] The triisocyanate, diluent monomer and drier are mixed, heated and kept warm, and then fatty alcohol is added to react, and then hydroxyl-containing acrylate monomer, aliphatic saturated polyester resin or polyether diol is added to continue the reaction to obtain the polyurethane acrylate resin.
[0028] Preferably, the heating is heating to 60-80°C, such as 60°C, 65°C, 70°C, 75°C or 80°C.
[0029] Preferably, the insulation is 0.5-1h, such as 0.5h, 0.8h or 1h.
[0030] Preferably, the reaction time is 0.5-2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.
[0031] Preferably, the continued reaction time is 2-4 h, such as 2 h, 3 h or 4 h.
[0032] In a third aspect, the present invention provides a use of the polyurethane acrylate resin as described in the first aspect in a central bendable glass coating.
[0033] Preferably, the polyurethane acrylate resin can be used in a coating for filling the groove of a central bendable glass.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects:
[0035] Compared with common polyurethane acrylate, the polyurethane acrylate resin prepared by the present invention using triisocyanate, fatty alcohol, aliphatic saturated polyester resin or polyether diol, diluent monomer, and hydroxyl-containing acrylate monomer as raw materials contains more side chains, a lower glass transition temperature, and better low-temperature bendability. The polyurethane acrylate resin provided by the present invention is prepared into UV glue for CFG groove filling. When the coating thickness is 150 μm, it is folded 200,000 times at -20°C, and the coating has no fogging, wrinkles, or breaks. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0037] The raw material information used in the examples and comparative examples of the present invention is as follows:
[0038] HDI trimer: Wanhua Chemical HT-100
[0039] Tetrahydrofuran acrylate: Changxing Chemical EM-214
[0040] Isooctyl alcohol: Chengdu Kelong Chemical Reagents
[0041] Hydroxyethyl acrylate: Guangdong Lankelu Chemical
[0042] Organic tin drier: Chengdu Cologne Chemicals
[0043] Polyester resin (molecular weight 1000 and 2000 respectively): Kunshan Custer Polymer Materials
[0044] Hydroxybutyl acrylate: Japan Osaka organic
[0045] HDI Biuret: Wanhua Chemical HB-100
[0046] Isophorone diisocyanate (IPDI): Wanhua Chemical
[0047] 4,4'-Dicyclohexylmethane diisocyanate (HMDI): Wanhua Chemical
[0048] Ethoxyethoxyethyl acrylate: Changxing Chemical EM211
[0049] Hexamethylene diisocyanate (HDI): Wanhua Chemical
[0050] Polypropylene glycol 2000: Chengdu Kelong Chemicals Co., Ltd.
[0051] Example 1
[0052] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0053] Under yellow light, 115 g of HDI trimer, 40 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Then, 26 g of isooctyl alcohol was added within 1 hour and the reaction was continued for 1 hour. Finally, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0054] Example 2
[0055] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0056] Under yellow light, 171 g of HDI trimer, 70 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 60° C. in a water bath for insulation. Then, 39 g of isooctyl alcohol was added within 1 hour and the reaction was continued for 0.5 hours. Finally, 23 g of hydroxyethyl acrylate and 400 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 4 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0057] Example 3
[0058] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0059] Under yellow light, 171 g of HDI trimer, 48 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 80° C. in a water bath for insulation. Then, 39 g of isooctyl alcohol was added within 30 minutes and the reaction was continued for 0.5 hour. Finally, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 1000 were added and the reaction was continued for 2 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0060] Example 4
[0061] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0062] Under yellow light, 171 g of HDI trimer, 70 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Then, 39 g of isooctyl alcohol was added within 1 hour and the reaction was continued for 1 hour. Finally, 23 g of hydroxyethyl acrylate and 400 g of polypropylene glycol 2000 were added and the reaction was continued for 3 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0063] Example 5
[0064] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0065] Under yellow light, 115 g of HDI trimer, 41 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Then, 26 g of isooctyl alcohol was added within 1 hour and the reaction was continued for 1 hour. Finally, 30 g of hydroxybutyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0066] Example 6
[0067] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0068] Under yellow light, 115 g of HDI biuret, 40 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Then, 26 g of isooctyl alcohol was added within 1 hour and the reaction was continued for 1 hour. Finally, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0069] Example 7
[0070] In this embodiment, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0071] Under yellow light, 115 g of HDI trimer, 40 g of ethoxyethoxyethyl acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Then, 26 g of isooctyl alcohol was added within 1 hour and reacted for 2 hours. Finally, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 hours. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0072] Comparative Example 1
[0073] In this comparative example, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0074] Under yellow light, 45 g of isophorone diisocyanate, 30 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Subsequently, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 h. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0075] Comparative Example 2
[0076] In this comparative example, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0077] Under yellow light, 53 g of 4,4'-dicyclohexylmethane diisocyanate HMDI, 31 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed and added into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation, followed by adding 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000, and the reaction was continued for 3 h, and the mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0078] Comparative Example 3
[0079] In this comparative example, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0080] Under yellow light, 34 g of hexamethylene diisocyanate HDI, 29 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation. Subsequently, 23 g of hydroxyethyl acrylate and 200 g of a polyester resin with a molecular weight of 2000 were added and the reaction was continued for 3 h. The mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0081] Comparative Example 4
[0082] In this comparative example, a polyurethane acrylate resin is provided, and the preparation method is as follows:
[0083] Under yellow light, 80 g of 4,4'-dicyclohexylmethane diisocyanate HMDI, 56 g of tetrahydrofuran acrylate, and 0.02 g of an organic tin drier were weighed and added into a three-necked flask, stirring was started, and the mixture was heated to 70° C. in a water bath for insulation, followed by adding 23 g of hydroxyethyl acrylate and 400 g of a polyester resin with a molecular weight of 2000, and the reaction was continued for 3 h, and the mixture was cooled to room temperature to obtain the polyurethane acrylate resin.
[0084] The polyurethane acrylate resins of Examples 1-7 and Comparative Examples 1-4 were tested for performance, and the testing method was as follows:
[0085] (1) using a rotational viscometer to test the viscosity of the polyurethane acrylate resin at 23° C. to obtain the resin viscosity;
[0086] (2) adding 1% initiator TPO and 1% initiator 184 to the prepared polyurethane acrylate resin, and testing the glass transition temperature of the cured product using a DSC tester after film curing;
[0087] (3) The prepared polyurethane acrylate resin was mixed with hydroxybutyl acrylate, isobutyl acrylate, tetrahydrofuran acrylate, and carboxyethyl acrylate in a ratio of 40:20:20:15:5, and 1% of the total weight of 184 photoinitiator and 1% of TPO were added and dissolved evenly to prepare a finished glue, which was coated on the primed CFG by film curing. After film curing, the surface scratch resistance was tested, and a hundred-grid test was performed after boiling in water for 1 hour. The bending radius R=1.5mm was folded 200,000 times at low temperature at -20°C (the coating thicknesses were 50 μm, 75 μm, 100 μm, 125 μm, and 150 μm, respectively);
[0088] Scratch resistance of finished glue: A 6B pencil is slid on the coating surface with a load of 50g. If there is no indentation or it can be recovered after sliding, it is judged to be OK. If there is a scratch, it is expressed as 1-5 levels, and the higher the level, the more serious the scratch;
[0089] Boiled water test: Boil at 95℃ for 1 hour, then place for 30 minutes and test the water according to the national standard;
[0090] Low temperature bending properties: CFG coated with different adhesive layer thicknesses was subjected to 200,000 R1.5 external folding tests at -20℃ on a book-turning bending machine.
[0091] The performance test results are shown in Table 1.
[0092] Table 1
[0093]
[0094] It can be seen from Table 1 that the polyurethane acrylate resin provided in Examples 1-7 of the present invention is prepared into UV glue for CFG groove filling, and the coatings have good scratch resistance and low-temperature bending properties (when the coating thickness is 150 μm and it is folded 200,000 times at -20°C, there is no fogging, wrinkles, or breaks in the coating).
[0095] When the polyurethane acrylate resin provided in Comparative Examples 1-4 was prepared into UV glue for CFG groove filling, the low-temperature bending properties of the coating were poor.
[0096] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the polyurethane acrylate resin and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyurethane acrylate resin, characterized in that: The raw materials for preparing the polyurethane acrylate resin include triisocyanate, fatty alcohol, aliphatic saturated polyester resin or polyether diol, diluent monomer, and hydroxyl-containing acrylate monomer.
2. The polyurethane acrylate resin according to claim 1, characterized in that The triisocyanate includes hexamethylene diisocyanate trimer and / or hexamethylene diisocyanate biuret.
3. The polyurethane acrylate resin according to claim 1 or 2, characterized in that: The fatty alcohol is a monofunctional alcohol, including any one or a combination of at least two of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol or an alcohol with a carbon number of 5-18, preferably any one or a combination of at least two of a branched alcohol with a carbon number of 4-18.
4. The polyurethane acrylate resin according to any one of claims 1 to 3, characterized in that The number average molecular weight of the aliphatic saturated polyester resin is 200-4000, preferably 500-2000; The number average molecular weight of the polyether diol is 200-4000, preferably 500-2000.
5. The polyurethane acrylate resin according to any one of claims 1 to 4, characterized in that The diluent monomer is a monofunctional acrylate that does not react with isocyanate or hydroxyl; Preferably, the diluent monomer comprises tetrahydrofuran acrylate and / or ethoxyethoxyethyl acrylate; Preferably, the hydroxyl-containing acrylic acid ester monomer includes any one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, caprolactone acrylate or caprolactone methacrylate, or a combination of at least two thereof.
6. The polyurethane acrylate resin according to any one of claims 1 to 5, characterized in that The molar ratio of the fatty alcohol to the triisocyanate is 1:(0.9-1.1), preferably 1:
1.
7. The polyurethane acrylate resin according to any one of claims 1 to 6, characterized in that The raw materials for preparing the polyurethane acrylate resin also include a drying agent; Preferably, the drier comprises an organotin drier and / or an organobismuth drier.
8. A method for preparing the polyurethane acrylate resin according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The triisocyanate, diluent monomer and drier are mixed, heated and kept warm, and then fatty alcohol is added to react, and then hydroxyl-containing acrylate monomer, aliphatic saturated polyester resin or polyether diol is added to continue the reaction to obtain the polyurethane acrylate resin.
9. The preparation method according to claim 8, characterized in that: The heating is heating to 60-80° C. Preferably, the insulation is 0.5-1h; Preferably, the reaction time is 0.5-2h; Preferably, the continued reaction time is 2-4 hours.
10. Use of the polyurethane acrylate resin according to any one of claims 1 to 7 in a central bendable glass coating.
Citation Information
Cited By
Preparation method of easy-to-peel transfer film
CN121912729A
A method for preparing an easily peelable transfer film
CN121912729B